13th Arctic Ungulate Conference, 22-26 August 2011, Yellowknife, Canada - Åhman (editor in chief), Birgitta; Wiklund (technical editor), Eva; Hegel (issue editor), Troy (Rangifer, 2013)
The 13th International Arctic Ungulate Conference was held in Yellowknife, Northwest Territories, Canada, from 22-26 August 2011. This biennial conference is the primary venue for meetings of the International Arctic Ungulate Society. Over 200 delegates attended the conference with representation from Canada, the United States, Norway, Sweden, Greenland, Finland, Russia, and Japan. The theme of the conference was “Challenges of Managing Northern Ungulates”. The goal of the conference organizers was to address the difficulties of managing ungulate populations that are faced with the unpredictable effects of climate change and an ever-increasing human presence on the land. The conference also focussed on the challenges associated with developing recovery actions for declining caribou and reindeer populations that are an integral part of Aboriginal cultures and ways of life.<!--[endif] -->